Xeroderma Pigmentosum C (XPC) Mutations in Primary Fibroblasts Impair Base Excision Repair Pathway and Increase Oxidative DNA Damage - Fayyad, Nour; Kobaisi, Farah; Beal, David; Mahfouf, Walid; Ged, Cécile; Morice-Picard, Fanny; Fayyad-Kazan, Mohammad; Fayyad-Kazan, Hussein; Badran, Bassam; Rezvani, Hamid R.; Rachidi, Walid (Frontiers in Genetics, 2020)
Xeroderma Pigmentosum C (XPC) is a multi-functional protein that is involved not only in the repair of bulky lesions, post-irradiation, via nucleotide excision repair per se but also in oxidative DNA damage mending. Since base excision repair (BER) is the primary regulator of oxidative DNA damage, we characterized, post-UVB-irradiation of primary fibroblasts, the detailed effect of different XPC mutations on mRNA, and protein activity levels of different BER factors. We found that XP-C fibroblasts are characterized by downregulated expression different BER factors including OGG1, MYH, APE1, LIG3, XRCC1, and Polβ. This was accompanied with an increase in DNA oxidative lesions, as monitored by 8-oxoguanine levels, instantaneously post-UVB-irradiation. These oxidative lesions persisted over time in XP-C cells having lower excision repair capacities but not in normal control cells. Taken together, our results indicated that an impaired BER pathway in XP-C fibroblasts leads to longer persistence and delayed repair of oxidative DNA damage. This might explain the diverse clinical phenotypes in XP-C patients suffering from cancer in both photo-protected and photo-exposed areas. Therapeutic strategies based on reinforcement of BER pathway might therefore represent an innovative path for limiting the drawbacks of nucleotide excision repair (NER)-based diseases, as in XP-C case.